The Effect of Low Preoperative Ejection Fraction on Mortality After Cardiac Surgery in Indonesia - Kurniawaty, Juni (Dove Medical Press Ltd, 2022)
Background: Among cardiac surgery patients, low preoperative left ventricular ejection fraction (LVEF) is common and has been associated with poor outcomes. The objective of this study was to assess the association between LVEF and postoperative mortality in patients undergoing open-heart surgery in several hospitals in Indonesia. Methods: We conducted a multicenter study with the retrospective design using data from patients undergoing open-heart surgery in 4 institutions in Indonesia. Data regarding LVEF and other potential risk factors were extracted from medical records and compiled in one datasheet. Statistical analyses were performed to assess if low LVEF was associated with postoperative mortality and identify other potential risk factors. Results: A total of 4789 patients underwent cardiac surgery in participating centers during the study period. Of these, 189 subjects (3.9) had poor preoperative LVEF. Poor LVEF was associated with postoperative mortality (adjusted OR 2.761, 95 CI 1.763– 4.323, p < 0.001). Based on types of surgery, LVEF had a significant association with mortality only in CABG patients, while there was no such association in valve surgery and inconclusive in congenital surgery patients. Other significant independent predictors of in-hospital mortality included age more than 65 years old, non-elective surgery, the complexity of procedures, history of cardiac surgery, organ failure, CARE score ≥ 3, NYHA class ≥ III, and poor right ventricular function. Conclusion: Patients with low preoperative LVEF undergoing open-heart surgery had a higher risk of postoperative mortality. Cardiac surgery can be performed with acceptable mortality rates. Accurate selection of patients, risk/benefit evaluation, and planning of surgical and anesthesiological management are mandatory to improve outcomes. © 2022 Kurniawaty et al.